2021
DOI: 10.1136/bmjopen-2021-049356
|View full text |Cite
|
Sign up to set email alerts
|

Coronavax: preparing community and government for COVID-19 vaccination: a research protocol for a mixed methods social research project

Abstract: IntroductionAhead of the implementation of a COVID-19 vaccination programme, the interdisciplinary Coronavax research team developed a multicomponent mixed methods project to support successful roll-out of the COVID-19 vaccine in Western Australia. This project seeks to analyse community attitudes about COVID-19 vaccination, vaccine access and information needs. We also study how government incorporates research findings into the vaccination programme.Methods and analysisThe Coronavax protocol employs an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Detailed methods for the Coronavax study have previously been published in the study's open access protocol. [44] In brief, recruitment of WA-based HCWs commenced in February 2021 when the project's data collection phase began, using media promotion, word-of-mouth and snowballing. Interested individuals signed up via an online REDCap ([ 44 , 45 ]) survey, which collected demographic data and contact details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed methods for the Coronavax study have previously been published in the study's open access protocol. [44] In brief, recruitment of WA-based HCWs commenced in February 2021 when the project's data collection phase began, using media promotion, word-of-mouth and snowballing. Interested individuals signed up via an online REDCap ([ 44 , 45 ]) survey, which collected demographic data and contact details.…”
Section: Methodsmentioning
confidence: 99%
“… [44] In brief, recruitment of WA-based HCWs commenced in February 2021 when the project's data collection phase began, using media promotion, word-of-mouth and snowballing. Interested individuals signed up via an online REDCap ([ 44 , 45 ]) survey, which collected demographic data and contact details. Prospective participants identifying as working in “health care and social assistance,” were contacted up to three times each by telephone and / or email to organise a face-to-face or telephone interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavax was initiated in April 2020 with the aim of ascertaining community attitudes towards vaccination and vaccine access in WA through a series of qualitative interviews with segmented population groups. A key aspect of the project involved translating findings to the state and federal governments in real‐time via Functional Dialogues, a novel formal research exchange mechanism in which data on community attitudes are presented to government officials, who then contribute their own reflections and experiences as additional research data (not reported here) 12 . Coronavax received ethics approval from the Child and Adolescent Services (CAHS) Human Research Ethics Committee (RGS0000004457).…”
Section: Methodsmentioning
confidence: 99%
“…We used social network analysis and digital trace data to examine the origin and spread of rumours about adverse events following COVID-19 vaccinations, presented as narrative case studies. This study sits within “Coronavax: Preparing Community and Government,” which seeks to uncover the conditions for a successful vaccination program in Western Australia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%